2021
DOI: 10.3390/healthcare9010085
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Oral Health-Related Quality of Life in Patients Attending Surgical Removal of Mandibular Third Molar Teeth

Abstract: The study aimed to measure the pre-operative oral health-related quality of life (OHRQoL) and to identify patient and teeth pathologies associated with worse OHRQoL among patients attending mandibular third molar tooth extraction. Data were collected preoperatively from 199 patients attending surgical removal of their mandibular third molar. To that end, we measured the Oral Health Impact Profile-14 (OHIP-14) and analyzed its association with: (1) demographics; (2) health-related behaviors such as smoking, alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
5
0
3
Order By: Relevance
“…Patient's perception of recovery is also influenced by patient-related predictors, past dental experiences as well as psychological and psychosocial factors, which are rarely assessed [22][23][24][25][26]. Psychologic distressed, high level of anxiety and impaired perception of OHRQoL seem to have a negative impact on postsurgical recovery [22][23][24][25][26].…”
Section: Monthmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient's perception of recovery is also influenced by patient-related predictors, past dental experiences as well as psychological and psychosocial factors, which are rarely assessed [22][23][24][25][26]. Psychologic distressed, high level of anxiety and impaired perception of OHRQoL seem to have a negative impact on postsurgical recovery [22][23][24][25][26].…”
Section: Monthmentioning
confidence: 99%
“…Patient´s perception of recovery and assessment of OHRQoL in conjunction with MSFA are seldomly reported [15][16][17][18][19][20][21]. Previous studies have indicated that patient´s perception of recovery is influenced by patientrelated predictors, incidence and severity of complications, presurgical expectations, past dental experiences as well as psychological and psychosocial factors [22][23][24][25][26]. Presurgical psychologic distress, high level of anxiety and impaired perception of OHRQoL seem to have a negative impact on patient´s perception of recovery [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os benefícios da cirurgia de terceiros molares estão o alívio da dor, prevenção da cárie dentária, da doença periodonta l, da formação de cistos, da reabsorção radicular dos segundos molares adjacentes, promoção do tratamen to ortodôntico e diminuição de riscos durante cirurgia ortognática (Cutilli et al, 2013;Cunha-Cruz et al, 2014;Lee et al, 2015;Abramovitz et al, 2021).Presença de dor, formação de cistos e reabsorção radicular foram os achados clínicos e radiográficos do presente estudo, o que evidencia a importante tomada de decisão para a remoção, de forma preventiva, dos terceiros molares.…”
Section: Discussionunclassified
“…As estimativas são que 54% dos terceiros molares inferiores são removidos profilaticamente sem a presença de quaisquer sintomas subjetivos, e 30 -50% dos terceiros molares referidos são removidos sem quaisquer indicações válidas. Diante desses dados, fica evidente que existe a necessidade de um diagnóstico bem realizado através de parâmetros clínicos, bem como através de exames complementares, para que se possa aplicar uma odontologia baseada em evidências (Abramovitz et al, 2021). Outro fator importante a ser considerado no momento do planejamento de exodontia de terceiros molares, é a idade do paciente.…”
Section: Discussionunclassified